RESPON PEMBACA TERHADAP KUMPULAN CERPEN SEPEDA DARI PRESIDEN KARYA YULISMAR - Nada Utari; M. Nur Mustafa; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This paper aims to describe the response of interest and convenience of junior high school students in Pekanbaru in understanding the contents of a collection of short stories Bicyclefrom the President of Yulismar's work who are mid-level winners at the Basic and Intermediate Literacy Material Writer Competition held by the KEMENDIKBUD Language Development and Language Development Board together with the Language Hal in 2018, via questionnaires to 50 SMP / MTS students in Pekanbaru who were randomly taken. As well as describing the values of education contained in the collection of short stories. This study resulted in the finding that this collection of Bicycle from the President storiesreceived a high positive response from readers, namely as many as 1159 of the 1400 positive reactions. And the educational value contained in it was also quite high for the category of a book containing 7 short stories that can be found in 92 educational values. So that the book collection of short stories Bicycle from the President of Yulismar's works is included in the feasible category with repairs as intermediate level reading material, because it not only meets the criteria of reader interest, but also fulfills the readiness requirements for the age level and quality in the educational value.Key Words: Literary reception, readers, educational value.